Proteins associated with cork formation in Quercus suber L. stem tissues. - Ricardo, Cândido P P; Martins, Isabel; Francisco, Rita; Sergeant, Kjell; Pinheiro, Carla; Campos, Alexandre; Renaut, Jenny; Fevereiro, Pedro (Journal of proteomics, 2011)
Cork (phellem) formation in Quercus suber stem was studied by proteomic analysis of young shoots of increasing age (Y0, Y1 and Y4) and recently-formed phellem (Y8Ph) and xylem (Y8X) from an 8-year-old branch. In this study 99 proteins were identified, 45 excised from Y8X and 54 from Y8Ph. These ones, specifically associated with phellem, are of "carbohydrate metabolism" (28%), "defence" (22%), "protein folding, stability and degradation" (19%), "regulation/signalling" (11%), "secondary metabolism" (9%), "energy metabolism" (6%), and "membrane transport" (2%). The identification in phellem of galactosidases, xylosidases, apiose/xylose synthase, laccases and diphenol oxidases suggests intense cell wall reorganization, possibly with participation of hemicellulose/pectin biosynthesis and phenol oxidation. The identification of proteasome subunits, heat shock proteins, cyclophylin, subtilisin-like proteases, 14-3-3 proteins, Rab2 protein and enzymes interacting with nucleosides/nucleic acids gives additional evidence for cellular reorganization, involving cellular secretion, protein turnover regulation and active control processes. The high involvement in phellem of defence proteins (thioredoxin-dependent peroxidase, glutathione-S-transferase, SGT1 protein, cystatin, and chitinases) suggests a strong need for cell protection from the intense stressful events occurring in active phellem, namely, desiccation, pests/disease protection, detoxification and cell death. Identically, highly enhanced defence functions were previously reported for potato periderm formation.
Keywords: Cork; Phellem formation; Proteomics; Quercus suber stem; Suberisation

Temperature stress effects in Quercus suber leaf metabolism. - Chaves, Inês; Passarinho, José António P; Capitão, Cláudio; Chaves, Maria Manuela; Fevereiro, Pedro; Ricardo, Cândido P P (Journal of plant physiology, 2011)
Based on projections that climate changes are will intensify in the near future, it is important to understand how plants respond to climate. Consequently, we have been studying the effect of contrasting temperatures on leaf metabolism of Quercus suber, an important Mediterranean oak. Potted plants were grown under controlled conditions for 53 days at 28°C or 10°C. The accumulation of major soluble metabolites was analyzed by NMR. The relative levels of transcripts of genes encoding key enzymes of the shikimate and phenylpropanoid pathway (CS, PAL, CAD and ChS) were examined by means of quantitative, real-time RT-PCR. At 10°C, in the pre-existing leaves, the concentrations of sucrose, quercitol and catechin were higher, as were PAL and ChS transcripts. At 28°C, however, it was the concentration of quinic acid that was higher, as were the concentrations of CS and CAD transcripts. We conclude that contrasting temperatures greatly influence Q. suber metabolism and that a deeper analysis of the effects of more extreme temperatures is needed to understand the possible effects of temperature changes on Q. suber metabolism and physiology.
Keywords: Abiotic stress response; Cork oak; Phenol metabolism; Secondary metabolism